Enquête Ethnobotanique Auprès Des Tradipraticiens De Santé Des Régions De Niamey Et Tillabéri Au Niger: Données 2012-2017 - Jazy, Mamadou Aïssa; Karim, Saley; Morou, Boubé; Sanogo, Rokia; Mahamane, Saadou (European Scientific Journal, ESJ, 2017)
Introduction: In Niger, people employ the services of traditional health practitioners who use medicinal recipes and plants for primary health care. Scope: Identify medicinal plants for primary health care. Methods: An ethnobotanical survey was carried out in two regions of Niger, Tillabéri and Niamey, according to a questionnaire. Results: This study assessed the transmission of knowledge, understood the concept of dosage in traditional medicine, and established a repertoire of recipes and plants of the traditional pharmacopoeia. A total of 913 therapeutic recipes for 226 species belonging to 77 families were collected from 168 traditional practitioners. The species most frequently encountered are: Sclerocarya birrea, Acacia nilotica, Guiera senegalensis, Annona senegalensis, Combretum micranthum, Balanites aegyptiaca, Pennisetum americanum, Piliostigma reticulatum, Cassia sieberiana, Ziziphus mauritiana, Azadirachta indica, Cassia occidentalis, Anogeissus leiocarpus, Combretum glutinosum, Khaya senegalensis, Momordica balsamina, Tephrosia lupunifolia, Prosopis africana, Alysicarpus ovalifolius, Bauhinia rufescens. The most common among them is the Combretaceae (10.68%), followed by Fabaceae (9.67%), Caesalpiniaceae (8.49%), Mimosaceae (7.82%), and Anacardiaceae (5, 55%). Among these plants, 60 belonging to 31 families, including 6 new families, were recorded. Several pathologies were treated. The most frequent of them are digestive disorders, hemorrhoids. Conclusion: These plants will be subjected to experimental studies before the development of new phytomedicines.